UV irradiation as a comparable method to thermal treatment for producing high quality stabilized milk whey. (May 2019) - Buhler, Sofie; Solari, Federico; Gasparini, Alessandra; Montanari, Roberto; Sforza, Stefano; Tedeschi, Tullia
Abstract: Whey is a valuable by-product of the dairy industry, due to the high nutritional, biochemical and functional properties of the contained proteins. As for other dairy products, to guarantee the microbiological safety of whey, thermal treatments are generally used. However, these processes can have a significant impact on the quality of the product. Thus, in recent years, interest in the use of non-thermal treatments in the dairy industry is significantly grown. In the present work, the use of UV irradiation as stabilizing treatment has been investigated on whey obtained from the Parmigiano-Reggiano cheese production. Two treatments were tested: UV treatment "1" which is characterized by three passages and UV treatment "2" by six ones. On skimmed whey samples, microbiological tests showed UV treatment 2 and the thermal treatment have the same effectiveness on Enterobacteriaceae, but UV treatment 2 is more effective than thermal treatment on total viable counts. Molecular characterization of the protein and total amino acid content was used as markers for the quality of the product. The results highlight that UV treatment can be equivalent to thermal pasteurization in terms of microbiological stabilization, and better preserving the whey quality. Highlights: UV irradiation and pasteurization allow comparable microbiological stabilization. The impact of UV irradiation on whey protein precipitation is neglectable. UV irradiation do not alter the nutritional value of the whey.